Prospects for atomic magnetometers employing hollow core optical fibre - Ironside, Charlie; Seunarine, K.; Tandoi, G.; Luiten, A. (2012)
Presently, among the most demanding applications for highly sensitive magnetometers are Magnetocardiography (MCG) and Magnetoencephalography (MEG), where sensitivities of around 1pT.Hz -1/2 and 1fT.Hz -1/2 are required. Cryogenic Superconducting Quantum Interference Devices (SQUIDs) are currently used as the magnetometers. However, there has been some recent work on replacing these devices with magnetometers based on atomic spectroscopy and operating at room temperature. There are demonstrations of MCG and MEG signals measured using atomic spectroscopy These atomic magnetometers are based on chip-scale microfabricated components. In this paper we discuss the prospects of using photonic crystal optical fibres or hollow core fibres (HCFs) loaded with Rb vapour in atomic magnetometer systems. We also consider new components for magnetometers based on mode-locked semiconductor lasers for measuring magnetic field via coherent population trapping (CPT) in Rb loaded HCFs. © 2012 SPIE.